OBJECTIFIKASI DIRI TUBUH DAN EGO DIRI DALAM FOTO KONSEPTUAL - Adi, Purwastya Pratmajaya; Triadiputra, S Andre (Acintya, 2018)
Objectification is a way to block things that are not supposed to be objects, which often in practice is not generally realized by those who become objects or make them become objects. The human body that appears in photographic imagery in modern life, becomes an appropriate example of how the collective unconsciousness of objectification practices is carried out and produced continuously. This unconsciousness will have an impact on human inability to control and master, and in other perspectives it will also build negative representations of the body and itself. In this work the collective unconscious is accommodated by the ego which then becomes personal awareness, where personal awareness will be conceptualized in the picture frame. This artistic research is interested in conducting an in-depth investigation of the behaviors of unconsciousness of objectification, especially those relating to the human body and self, then explored and used as ideas and foundations for the creation of photographic works. The choice of approach to realize this idea, will use conceptual photography which emphasizes the expression or context of the personal interpretation of the photo artist on a phenomenon as the basis of ideas and main ideas in the creation of his photographic artwork.Keywords: Self Objectification, Body and Ego, Conceptual Photos